The council of the European Union and its geographical realm - Taghizadeh Ansari, Mustafa; Daryabeigi Balvardi, Keyvan (Opción, 2019)
The council of the European Union participates in all the decision-making processes as an active body. In this article, in addition to a separation between the Council of the European Union and some other organizations similar in name but different in function, the main features of the Council of the European Union will be declared and by means of some cases related to Europe’s foreign concerns and crises include Iran Nuclear Deal and Syrian Crisis; it becomes clear that the acts of the council of the EU is not limited to Europe’s territory, not in Eligibility nor in its interest.